1991
DOI: 10.1111/j.1600-0676.1991.tb00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological outcome in interferon alpha‐2b treated patients with chronic posttransfusion non‐A, non‐B hepatitis

Abstract: ABSTRACT— The histological outcome in liver biopsies following 9 months of interferon alpha‐2b treatment was assessed in detail in 19 patients with chronic posttransfusion non‐A, non‐B hepatitis (PTH‐NANB) and compared with 12 untreated PTH‐NANB patients. Fourteen (74%) treated and 7 (58%) control patients were reactive for antibodies against hepatitis C virus (anti‐HCV). Liver biopsies taken before and after the 9‐month period were scored numerically for portal inflammation, piecemeal necrosis (PMN) and fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Specimens from patients with NAFLD were evaluated to determine the grades and stages of steatosis (S0-S3), activity (A0-A3), ballooning (B0-B2), and fibrosis (F0-F4) according to the modified criteria of Kleiner (20). Specimens from patients with HCV were evaluated according to the histology activity index scoring system of Knodell et al (21) with the modifications proposed by Schvarcz et al (22) (for the categories of periportal necrosis and portal inflammation) and by Scheuer (23) (for the categories of lobular necroinflammation and fibrosis). The grading score for histological activity of chronic hepatitis represents the sum of the scores for their periportal, lobular, and portal lesions (24).…”
Section: Methodsmentioning
confidence: 99%
“…Specimens from patients with NAFLD were evaluated to determine the grades and stages of steatosis (S0-S3), activity (A0-A3), ballooning (B0-B2), and fibrosis (F0-F4) according to the modified criteria of Kleiner (20). Specimens from patients with HCV were evaluated according to the histology activity index scoring system of Knodell et al (21) with the modifications proposed by Schvarcz et al (22) (for the categories of periportal necrosis and portal inflammation) and by Scheuer (23) (for the categories of lobular necroinflammation and fibrosis). The grading score for histological activity of chronic hepatitis represents the sum of the scores for their periportal, lobular, and portal lesions (24).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed improvement in liver tissue when SVR is achieved after IFN-based therapy. In 1991, Schvarcz et al (28) evaluated liver tissue before and 9 months after IFN monotherapy and observed improvement in fibrosis, necrosis, and inflammation in liver tissue after therapy. Terada et al (29) found improvement of staging and grading to A0 (or A1) and F0 (or F1) three years after achievement of SVR.…”
Section: Discussionmentioning
confidence: 99%